2020
DOI: 10.3390/v12101134
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Pestivirus Heterogeneity and Its Potential Impact on Vaccination and Diagnosis

Abstract: Bovine Pestiviruses A and B, formerly known as bovine viral diarrhoea viruses (BVDV)-1 and 2, respectively, are important pathogens of cattle worldwide, responsible for significant economic losses. Bovine viral diarrhoea control programmes are in effect in several high-income countries but less so in low- and middle-income countries where bovine pestiviruses are not considered in disease control programmes. However, bovine pestiviruses are genetically and antigenically diverse, which affects the efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 95 publications
0
24
0
Order By: Relevance
“…In contrast to the NS3 ELISA response, all BVDV vaccines were able to induce a similar neutralizing antibody response against BDVD1a NADL strain after immunization of sheep, regardless of the genotypes 1a (Mucosiffa, Bovilis) or 1b (Bovela) of the vaccine strains. Induced detectable levels of cross-reacting antibodies against at least one other subgenotype have been previously described after BVDV-1 vaccination in cattle (for review, [ 37 ]) and BDV infection of sheep [ 9 , 11 , 16 ]. Our results however differ from those of Sozzi et al who showed that the BVDV-1b vaccine strain of Bovela did not induce neutralizing antibodies against the BVDV-1a NADL strain after immunization of cattle [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the NS3 ELISA response, all BVDV vaccines were able to induce a similar neutralizing antibody response against BDVD1a NADL strain after immunization of sheep, regardless of the genotypes 1a (Mucosiffa, Bovilis) or 1b (Bovela) of the vaccine strains. Induced detectable levels of cross-reacting antibodies against at least one other subgenotype have been previously described after BVDV-1 vaccination in cattle (for review, [ 37 ]) and BDV infection of sheep [ 9 , 11 , 16 ]. Our results however differ from those of Sozzi et al who showed that the BVDV-1b vaccine strain of Bovela did not induce neutralizing antibodies against the BVDV-1a NADL strain after immunization of cattle [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic and antigenic diversity of pestiviruses is well known and well documented in the literature. A good cross-protection has been observed within the wide range of BVDV-1 genotypes, as was cross-protection against BVDV-2 using BVDV-1 based MLV vaccines [ 37 , 39 ]. However, the inability to fully prevent fetal infection, postnatal infection, and virus shedding has, in part at least, been attributed to antigenic diversity [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the infections ofthis pathogen havingthe highest impact on livestock worldwide [ 1 , 11 ], it is still the case that neither effective vaccines nor selective antiviral drugs are available [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%